Money, Banks, and Savings: A Comparative Analysis of Turkish Laypeople’s Social Representations over Five Periods (1999-2017) - MİNİBAŞ-POUSSARD, Jale and BİNGÖL, Haluk Baran and ROLAND-LEVY, Christine and DİYARBAKIRLIOĞLU, Erkin and; in Celik, Tutku (International Journal of Contemporary Economics and Administrative Sciences, 2020)
The way and context-specific scope of how money and banks are mirrored in citizens’ minds is an expanding area of research in relation to economic psychology. Through the analysis of data collected from salaried employees, self-employed professionals, and small/medium enterprise [SME] owners, lay people’s social representations for money, saving and banks in Turkey are comparatively investigated and analysed over time. Grounded in a previous study by authors (undisclosed), with respective samples from the years of 1999, 2001, 2007, 2015, a new fifth dataset for 2017 is introduced here. Changing priorities, understanding and cognitive constructs related to money, banks and savings were particularly analysed to be substantially interconnected with the evolving socioeconomic dynamics and conditions of the crisis periods. Negative evocations and lack of trust became prominent as to the findings such that banks are seen as contemporary pawnshops; money is mirrored as a symbol of power, prestige and reputation, and cannot be achieved through hard work.